Penerapan Model Pembelajaran Inkuiri untuk Meningkatkan Motivasi dan Hasil Belajar Siswa pada Materi Cahaya dan Sifat-Sifatnya di SD Negeri 2 Uebone - Harni Harni (Universitas Pendidikan Mandalika, 2021)
This study aims to improve student motivation and learning outcomes through the application of inquiry learning models. The research method used was classroom action research that adapted the Kemmis & Mc. Model. Taggart with two cycles. The subjects of this study were students of grade IV SD Negeri 2 Uebone, totaling 28 students. Data collection techniques using tests, observation and documentation. The data validation used source triangulation and method triangulation techniques. The data analysis technique was processed by descriptive analysis. The results of research using the inquiry method showed that the motivation and learning outcomes of students had increased. The increase in student learning motivation from the initial conditions of 30% or 35.71% or 10 students increased to 18 students or 64.29% and reached 100% of the 85% minimum limit that had been determined in the success criteria of the learning improvement process in the second cycle, and the increase in student learning outcomes from the average in the initial conditions of 57.50 increased to 64.64 in the first cycle and at the end of the second cycle increased to 77.86 and the completeness of learning in the initial conditions was 6 students (21.43%), After the improvement was carried out by the application of the inquiry method in the first cycle it increased to 15 students or 53.57% and in the second cycle it increased again to 26 students or 92.86%.